Pengembangan Bahan Ajar Membaca Cepat Berbasis E-Learning (Studi Pengembangan Di SDN Tidung Kota Makassar) - Muh. Zuhdy Hamzah; Marwah Densi; Muhamad alfi khoiruman (JURNAL ILMU PENDIDIKAN (JURIP), 2022)
This research is a development research. The focus of the research was to develop e-Learning-based fast reading fiction text teaching materials for grade 5 students at SDN Tidung Makassar City. The subject of this research is a valid, practical, and effective fast-reading teaching material for fiction texts. The teaching material product development method uses the Four-D model development design from Thiagarajan which consists of four stages. The four stages are define, design, develop and disseminate. The results showed that the e-Learning-based fast reading of fictional texts for grade 5 students at SDN Tidung Makassar City was in the very valid category because the average expert validation results for the e-Learning-based fast reading of fictional texts reached the predetermined standard, in the very category. practical because the average value of the percentage of students who agreed with the statement items in the student response questionnaire was 99.46%, and very effective because the pretest results were in the incomplete category, while the posttest results were in the complete category.